Mapping the Research Landscape of Table Tennis Performance: A Bibliometric and Systematic Literature Review of Global Trends, Emerging Themes, and Future Research Directions - Hasnah Hasnah (Universitas Cahaya Prima, 2024)
This study presents a comprehensive bibliometric and systematic literature review of global research trends in table tennis performance from 2000 to 2024. Using Scopus and Web of Science databases, a total of 1,247 documents were retrieved and analyzed through VOSviewer and Bibliometrix software. The analysis encompasses publication trends, co-authorship networks, keyword clustering, and citation patterns across 89 countries. Findings reveal a significant acceleration in research output post-2015, with China, Germany, and Japan emerging as dominant contributors. Six major thematic clusters were identified: biomechanics and stroke technique, training methodology and periodization, physiological demands and fitness profiling, psychological factors and mental performance, technology-assisted coaching, and talent identification and youth development. The results indicate a growing emphasis on interdisciplinary approaches combining sports science, data analytics, and artificial intelligence in performance analysis. Emerging themes include wearable sensor applications, machine learning for stroke classification, and mental resilience frameworks. This review provides a structured overview of the field's evolution, identifies research gaps particularly in para-table tennis and long-term athlete development, and offers evidence-based recommendations for future research priorities. The findings are expected to guide scholars, coaches, and sports organizations in advancing the scientific understanding of table tennis performance.